The Development of Lower Vocational Schools in Niš from the End of the 19th Century until 1914 - Pešić, Miroslav D.; Ranđelović, Vojin N. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper provides a brief overview of the development of lower vocational schools in Niš from their establishment until 1914, i.e., until the beginning of the First World War. In that period, there were three lower vocational schools in Niš: the Trade School of the Niš Trade Youth, the Women’s Workers’ School of the Women’s Society, and the General Vocational Sunday-Holiday School. Despite the challenges it encountered during its establishment, the Trade School of the Niš Trade Youth began its work in 1893. As early as 1895, the Niš Trade Youth joined forces with the craftsmen, and the association became known as the Niš Trade-Craft Youth. The association and the school were suspended from 1897 to 1901 due to disagreements between merchants and craftsmen, but they continued to operate under the old name. The Women’s Workers’ School was founded in 1883 by the Niš branch of the Women’s Society through the use of its own finances. It was the women’s worker’s school for embroidery, white linen, and dresses, where the majority of classes were focused on professional subjects and practical work. The General Vocational Sunday-Holiday School was established in 1903 as an evening, weekly holiday general-type school. The General Vocational Sunday-Holiday School aimed to develop competent craftsmen-masters from students through theoretical, professional, and practical instruction. This paper considers the establishment of these schools, the problems they had to face, and their significance for the development of the city of Niš.
Keywords: school; the Niš Trade Youth; the Women’s Society; association; class